Increase of Cooling Capacity of Strawberry Canopy by Evaporative Cooling Together with Air Flow Controlling Under Culture Bench and Cool Water Tube - พุทธรักษา ภานุวิชญ์; Mongkon, Sulaksana (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This research aims to study the increase of cooling capacity for the nurture of canopy temperature in strawberry greenhouse that used evaporative cooling systems together with air flow controlling under the culture bench and cool water tube. The greenhouse had 6 m of width, 24 m of length and 4.8 m of height. The roof was covered by polyethylene plastic and insect screen net. On the north wall was installed the cooling pad of 14.04 m2 area. Inside greenhouse had the culture bench that was 0.3 m of width, 21 m of length and 1 m of height. The 50 W of ventilation fans were install every the culture benches. The cool water tube made from aluminum with a diameter of 1.27 cm, length of 21 m and used one return coil between the strawberry bush. The results showed that the air flow controlling could decrease the air temperature around the plant canopy to a maximum of 5.5 oC when compared with non-air flow controlling, and the use of cool water tube could not effect of cooling. For the mathematical model study, it was found that using the faster velocity fan together with the opening width increasing of air flow controlling could reduce the strawberry canopy temperature about 4 - 5 oC and the coefficient of performance increased by 66.12 %.